Cooperative Spin Excitations in Quantum Materials Studied by Neutron Spectroscopy - Gaw, S (2014)
This thesis describes the experimental investigation of three different strongly correlated transition-metal oxide systems. The magnetic behaviour of each has been probed using inelastic neutron spectroscopy. A distinctive hour-glass excitation spectrum has been observed in the layered cobaltate La1.75Sr0.25CoO4. This spectrum is similar to that measured in a related cobaltate La1.67Sr0.33CoO4, although it appears broader. The spectrum has been reproduced using a spin wave model derived from a disordered cluster spin glass ground state. Signatures of spin glass behaviour have also been observed in bulk magnetisation measurements of La1.75Sr0.25CoO4. These findings, once more, demonstrate the emergence of an hour-glass spectrum from a ground state that combines quasi-one dimensional magnetic correlations and disorder. Additionally, this study shows that charge and magnetic stripe order persists to lower dopings in La2-xSrxCoO4 than previously thought. The complete magnetic excitation spectrum of the multiferroic compound CuO has been measured for the first time. A high energy, one-dimensional magnetic spectrum is observed and modelled using the Muller ansatz derived for the S=1/2 Heisenberg antiferromagnetic chain. At lower energies, a three-dimension spectrum is observed. The measured spectrum is inconsistent with all previous theoretical estimates of the dominant inter-chain exchange interactions in CuO. The inter-chain dispersion is successfully described by a phenomenological model based on linear spin wave theory. The third material investigated, LuFe2O4 demonstrates complex charge and magnetic order, the precise nature of which is still under debate. The full spectrum of in-plane excitations in LuFe2O4 has been measured and a complicated dispersion consistent with six magnetic modes is observed. These findings are compatible with structures described by a magnetic unit cell containing six spins. The dispersion can be described by a spin wave model derived from a bilayer structure comprised of charge-rich and charge-poor monolayers. This structure is consistent with the original site-specific model for the 3D magnetic ordering in LuFe2O4.